Large-scale fermentation of Lactiplantibacillus pentosus 292 for the production of lactic acid and the storage strategy based on molasses as a preservative - Xing Chen; Zhirong Wei; Ziqiao Feng; Yuhan Che; Xinyi Wang; Hao Long; Xiaoni Cai; Wei Ren; Zhenyu Xie (BMC Microbiology, 2025)
Abstract Background Lactiplantibacillus pentosus 292 is a lactic acid bacterium (LAB) with significant probiotic potential, but large-scale production is often limited by high production costs and preservation challenges. This study aimed to develop a cost-effective medium to enhance lactic acid production and establish a feasible preservation strategy to support the strain’s large-scale application. Results A low-cost medium containing glucose, yeast powder, K₂HPO₄, and Tween-80 was formulated, enabling Lactiplantibacillus pentosus 292 to achieve a lactic acid yield of 16.24 g/L, representing an 83.48% increase compared to the traditional MRS medium. Fermentation kinetics models for bacterial growth, substrate consumption, and product generation were established in a 200-L fermenter using the Logistic, Luedeking-Piret-like, and Luedeking-Piret models, and the R 2 values from the model equation were 0.9921 (OD600nm), 0.9942 (dry weight), 0.9506 (total protein), 0.8383 (lactic acid), 0.8898 (total sugar), and 0.8585 (reducing sugar), respectively, indicating that these models were suitable for accurately simulating the growth, nutrient production, and substrate consumption of L. pentosus 292. Additionally, a preservation strategy was developed by using 1–3% molasses as a preservative for the fermentation broth, and its efficacy was verified through temperature acceleration experiments. Conclusion In this work, a cost-effective medium that significantly increased lactic acid yield and a preservative based on molasses as a strategy to extend the storage period of fermentation products were developed for large-scale production of L. pentosus 292, a member of probiotic LAB. Additionally, large-scale fermentation kinetics models were constructed, providing valuable technical insights for the large-scale production and application of this LAB, highlighting its significant potential for industrial applications.